DNS on Windows 2000 - Larson, Matt (O'Reilly, 2001)
DNS on Windows 2000 is a special Windows-oriented edition of the classic DNS and BIND. The Domain Name System (DNS) is one of the Internet's fundamental building blocks: the distributed host information database that's responsible for translating names into addresses, routing mail to its proper destination, and many other services. As the preface says, if you're using the Internet, you're already using DNS--even if you don't know it. Besides covering general issues like installing, setting up, and maintaining the server, DNS on Windows 2000 tackles those specific to the Windows environment: integration between DNS and Active Directory, conversion from BIND to the Microsoft DNS server, and registry settings. You'll also acquire a grounding in: Security issues System tuning Caching Zone change notification Troubleshooting Planning for growth What DNS does, how it works, and when you need to use it How to find your own place in the Internet's namespace Setting up name servers Integrating Active Directory with DNS Dynamic updates, storing zone information in Active Directory, and incremental zone transfers Using MX records to route mail Configuring hosts to use name servers Subdividing domains (parenting) Securing your name server: preventing unauthorized zone transfers Mapping one name to several servers for load sharing Troubleshooting: using nslookup, diagnosing common problems If you're a Windows administrator, DNS on Windows 2000 is the operations manual you need for working with DNS every day; if you're a Windows user who simply wants to take the mystery out of the Internet, this book is a readable introduction to the Internet's architecture and inner workings. Topics include